(untitled) (Revista Contexto & Saúde, 2023)
The present study performed the translation and assessment of the validity and reliability of the Male Body Attitudes Scale (MBAS) for Brazilian men. The steps of translation, synthesis of translation, back-translation, expert committee and pre-test were carried out. Then, the Brazilian version of the MBAS was applied to a sample of 454 undergraduate men, aged between 18 and 35 years. We evaluated the factor structure of the MBAS through confirmatory factor analysis (factorial validity), as well as the convergent validity by association tests between MBAS scores and symptoms of muscle dysmorphia, body dissatisfaction, drive for muscularity and psychological commitment to physical exercise. Reliability was estimated by internal consistency and test-retest stability, with an interval of two weeks. The Brazilian version of the MBAS upheld the original factor structure of the scale, composed of three factors (Musculature, Body Fat and Height) and 24 items, showing good fit indices (χ²/df = 3.523; CFI = 0.95; TLI = 0.95; SRMR = 0.06; and RMSEA = 0.06 [CI 95%: 0.06, 0.08; p = 0.019]). The MBAS also showed good convergent validity. We found adequate internal consistency (Cronbach’s alpha of 0.87) and test-retest stability (intraclass correlation coefficient of 0.89; p < 0.001), showing good reliability of the Brazilian version of the MBAS. It is concluded that the MBAS was translated and adapted for the Brazilian population and showed good psychometric qualities of validity and reliability in a sample of undergraduate men.